Developing Articulate Storyline (AR)-Based Learning Media through the Sunda Mandala Game for Teaching the Human Digestive System to Kasepuhan Citorek Indigenous Students in Banten - Darmawa, Indra; Miharja, Jajang; Sari, Mutiara; Eka Nur Fitriana, Desi (Biosfer: Jurnal Tadris Biologi, 2025)
Student learning achievement, especially in biology material, is still low. One of the causes is the lack of interesting and contextual teaching materials on local culture. This study aims to develop Articulate Storyline (AR) learning media with the Sunda Mandala game on the human digestive system for students of the Kasepuhan Citorek, Banten. The research method uses Research and Development (R&D) with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The sample taken in this study was 30 students of class XI MIPA 1 at Senior High School. Data collection techniques in this study used interview and questionnaire techniques. The results of the study showed that the feasibility value of interactive learning media based on an articulate storyline on the human digestive system material from material experts was 93.75% with a very feasible category, the results of media expert assessments were 85% with a feasible category, and the results of language expert assessments were 85% with a feasible category. The results of the trial data analysis showed that student responses were 83.9%, categorized as very good. Pengembangan Media Pembelajaran Articulate Stroryline (AR) dengan game Sunda Mandala Pada Materi Sistem Pencernaan Manusia untuk Siswa Adat Kasepuhan Citorek, Banten ABSTRAK: Prestasi belajar siswa khususnya materi biologi masih rendah. Salah satu penyebabnya adalah kurangnya bahan ajar yang menarik dan kontekstual dengan budaya lokal.Penelitian ini bertujuan mengembangkan media pembelajaran Articulate Stroryline (AR) dengan game Sunda Mandala materi sistem pencernaan manusia pada siswa/i adat kasepuhan Citorek, Banten.  Metode penelitian menggunakan Research and Development (R&D) dengan model ADDIE (Analyze, Design, Development, Implementation, Evaluation). Sampel yang diambil dalam penelitian ini yaitu siswa kelas XI MIPA 1 di Sekolah Menegah Atas sebanyak 30 siswa. Teknik pengumpulan data dalam penelitian ini menggunakan teknik wawancara dan angket. Hasil penelitian menunjukkan bahwa nilai kelayakan media pembelajaran interaktif berbasis articulate storyline pada materi sistem pencernaan manusia dari ahli materi sebesar 93,75% dengan kategori sangat layak, hasil penilaian ahli media sebesar 85% dengan kategori layak dan hasil penilaian ahli bahasa sebesar 85% dengan kategori layak. Hasil analisis data uji coba respon siswa didapatkan sebesar 83,9% dengan kategori sangat baik.